A new antimicrobial indoloditerpene from a marine-sourced fungus aspergillus versicolor ZZ761. Issue 18 (17th September 2021) - Zhang, Di; Yi, Wenwen; Ge, Hengju; Zhang, Zhizhen; Wu, Bin
Abstract: A new indoloditerpene (1 ) and fifteen known compounds (2 –16 ) were isolated from a marine-derived fungus Aspergillus versicolor ZZ761. Structure of the new compound was elucidated as (3  R, 9 S, 12 R, 13 S, 17 S, 18 S )-2-carbonyl-3-hydroxylemeniveol based on its HRESIMS data, NMR spectroscopic analyses, the Mosher′s method, and ECD calculation. This new indoloditerpene (1 ) showed antimicrobial activities with MIC values of 20.6 μM against Escherichia coli and 22.8 μM against Candida albicans . Diorcinol (2 ) and versicolorin B (6 ) had activities in inhibiting the proliferation of human glioma U87MG and U251 cells with IC50 values of 4.4 and 6.2 μM and 11.3 and 30.5 μM, respectively. Graphical Abstract: